Patients’ attitude towards medical students at Combined Military Hospital, Dhaka - Begum, Nasrin; Nasrin, Afsana; Rahman, Mohammad Maksudur; Islam, Md Tanvirul (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Patient is the best resource and most important component in medical education. One of the vital parts of clinical education is patients’ cooperation and acceptance of medical students in their care. Aim: To assess patients’ attitude towards medical students at Combined Military Hospital (CMH) Dhaka, and to determine factors that may affect those attitudes. Methods: This cross-sectional study was conducted at CMH Dhaka, an affiliated teaching hospital to Armed Forces Medical College (AFMC). One hundred and eighteen patients were interviewed face to face from January to June 2021 using a predesigned questionnaire. Results: All study participants had responded to the questionnaire. Majority of the patients (98%) thought that students should examine patients as part of their medical training. All participants accepted students’ presence during the medical consultation. 86.4% and 69.5% of the patients agreed students’ involvement in general physical examination in presence and absence of a doctor respectively. In case of genital examination by students 33.9% and 30.5% patients were agreed to allow them in presence and absence of supervising doctor respectively. Conclusion: Patients of this study show some overall positive attitudes. Patients like less number of students' involvement in their physical examination; however, majority of the patients realized the importance of patient examination by students as a part of their medical training. JAFMC Bangladesh. Vol 17, No 2 (December) 2021: 12-16